ISLAM DAN ILMU PENGETAHUAN DALAM PERSPEKTIF FILSAFAT ILMU: KAJIAN ONTOLOGIS, EPISTEMOLOGIS, DAN AKSIOLOGIS - Samsul Maarif Subaer; Mukasyifah Damis; Nurul Qalbi (Halaqah: Journal of Multidisciplinary Islamic Studies, 2026)
Science and religion are two essential elements in human life that are closely related and complementary. In Islam, science occupies a crucial position as a means of understanding reality, knowing Allah SWT, and realizing the welfare of humanity. This article aims to examine the meaning of Islam and science and analyze their relationship from the perspective of the philosophy of science. This research uses a qualitative approach with a literature study method. Data were obtained through the analysis of various written sources, such as books and relevant scientific articles, then analyzed descriptively and analytically. The results of the study indicate that science from the perspective of the philosophy of science is understood through three main aspects: ontology, epistemology, and axiology. Islam views science not only as a rational and empirical activity, but also as a spiritual means based on the value of monotheism. Ontologically, Islam recognizes reality that encompasses empirical and metaphysical dimensions. Epistemologically, Islam integrates revelation, reason, and empirical experience as complementary sources of knowledge. Axiologically, science is directed towards moral values, justice, and human welfare. Thus, the relationship between Islam and science is harmonious and complementary, so that the integration of the two becomes an important foundation in building a civilization that is scientifically advanced and morally and spiritually dignified.